Cost analysis of registered brands of oral antidepressant drugs in Pakistan: a descriptive analysis. (2nd September 2020) - Kamran, Sohail; Saqlain, Muhammad; Khan, Zakir; Mahmood, Sajid; Ali, Hussain; Ahmad, Nafees; Shah, Kifayat Ullah
ABSTRACT: Background and objective : Depression is a global public health threat, and its treatment constitutes drugs in psychopharmacology, a domain that is rapidly growing with the addition of newer agents in market that are of high cost. Therefore, the present study aims to investigate the number of registered brands and price variation of oral antidepressants in Pakistan. Methods : A descriptive observational study was carried out to analyze the cost of oral antidepressants in Pakistan. Pharma guide 2019 was used to derive the cost of antidepressants marketed in Pakistan. The details about the number of registered brands and maximum and minimum prices of antidepressant drugs were calculated. Results : Sixteen drugs in 38 formulations were registered in 607 brands in Pakistan. Variations among 38 different formulations range from 0% to 746.39%. Out of these 38 formulations, 31 had variations below 200%, while 7 formulations had price variation above 200%. The highest price (746.39%) variation was observed for citalopram 20 mg (price per tablet PKR 6.79 to PKR 57.47) and no (0%) price variation was for bupropion 75 mg (price per tablet PKR 10). Conclusion : The study revealed wide variations in the number of registered brands and prices of oral tablets of antidepressants in Pakistan. The government needs to devise effective strategies to implement established policies to ensure uniformity in price, quality, and effectiveness with the ultimate goal to reduce treatment cost. Also, measures should be taken to inform prescribers about cost variation of drugs as prerequisite for cost-effective treatments to ultimately reduce treatment cost and financial burden and improve patient's adherence to therapy.